An Analysis of Imagery on Collections of Poems Written by Robert Frost - Rosalina Pitaloka; Ayu Oktaviani; Ani Fiani (EDULIA: English Education, Linguistic and Art Journal, 2023)
The problem of this study is: “What kinds of imagery are used in the collection of Robert Frost’s poems?”. Therefore, the objective of this study is to describe the kinds of imagery in Robert Frost’s poems entitled “After Apple-Picking, Stopping by Woods on a Snowy Evening, The Road Not Taken, To Earthward, Wind and Window Flower, Out-Out, Fire and Ice, Nothing Gold Can Stay, Acquainted with the Night, and A Time To Talk”. The writer used content analysis to classify and analyze the data. The approach used in collecting the data was descriptive qualitative. After investigating the kinds of 10 collections of poems written by Robert Frost, the writer found 95 imagery. The imagery in Robert Frost’s poems has been analyzed in kinds: (1) 37 visual, (2) 20 auditory, (3) 17 kinesthetic, (4) 9 organic, (5) 5 olfactory, (6) 4 tactile, and (7) 3 gustatory. Keywords: Analysis, Imagery, Poems, Robert Frost